Percepção dos alunos do curso de Ciências Contábeis da Universidade Federal da Paraíba sobre o mercado financeiro brasileiro - Andrade, Matheus Eduardo Oriente (2020)
There are several possibilities and opportunities for short, medium and long-term financial investments through the financial market, making financial management a mechanism for generating personal wealth. The objective of this study is to identify the knowledge of students in the Accounting Sciences course at Universidade Federal da Paraíba (UFPB) regarding the financial market. In the data collection, an online questionnaire was applied through the “google forms”, then the physical questionnaires were applied in the classrooms in the morning and night shifts with the students of the Accounting Sciences course at the Federal University of Paraíba, which was the main source of data collection, which added to the questionnaires applied electronically constituted a total sample of 126 students. The results point to a lack of knowledge about the financial market by the students and a well-divided investor profile, with the majority containing an aggressive investor profile, showing preference for investments in shares and stock funds, a low familiarity with certain types of financial investments and the main channel as a source of information, the internet.